Assessment of Trace Elements in Water, Sediments, and Fish Tissues from the Al-Gharraf River - Afrah Abid Maktoof; Marwa Kadhim Katia; Sarah A Sayer (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Trace elements are persistent environmental contaminants that accumulate in aquatic systems and pose ecological and health risks. Specific Background: The Al-Gharraf River in southern Iraq receives inputs from agricultural, industrial, and domestic activities, increasing concern about metal enrichment in water, sediments, and fish. Knowledge Gap: Despite regional studies, data on the simultaneous distribution and bioaccumulation of cadmium and zinc in multiple environmental compartments of this river remain limited. Aims: This study assessed concentrations of cadmium and zinc in water, sediments, and fish tissues across three months to determine contamination levels and ecological implications. Results: Findings showed pronounced elevation of both metals in December compared with November and January, with the highest accumulation recorded in sediments and in fish gills and liver, while muscles exhibited comparatively lower concentrations. The consistent month-to-month variation demonstrated active metal inputs and dynamic environmental interactions that facilitate bioaccumulation. Novelty: This study provides integrated, compartment-based evidence of trace-metal distribution in a key river system using synchronized sampling of water, sediment, and multiple fish tissues. Implications: The results underscore the urgent need for strengthened monitoring and management strategies to mitigate metal pollution and safeguard ecosystem integrity and public health.Highlight : Shows increased cadmium and zinc levels in December across all sample types. Fish organs, especially gills and liver, display clear bioaccumulation patterns. The findings underline the need for stricter environmental monitoring. Keywords : Trace Metals, Al-Gharraf River, Water, Sediments, Fish Tissues